Prevalence of non-infectious dermatoses in patients attending a tertiary care center in Rajasthan - Singh, Bhagirath; Paul, Indira Subhadarshini (International Journal of Research in Dermatology, 2019)
Background: Pediatric dermatoses require a separate view from adult dermatoses as there are important differences in clinical presentation, treatment and prognosis. There is very little epidemiological study available on non-infectious childhood dermatoses in India. The aims of the study were to find the prevalence, clinical profile and various etiological factors associated with childhood non-infectious dermatoses and to determine the prevalence of most common non-infectious childhood dermatoses. Methods: This cross-sectional observational study conducted at tertiary care centre in Rajasthan, India. Children with age 13 years and below with clinical evidence of cutaneous disorders were studied. Parents who have not given consent for the study, acutely ill children, Children having infectious dermatoses (bacterial, fungal, viral, arthropods, parasitic and protozoal infection) were excluded from the study. Results: A total of 232 cases were studied which showed a female preponderance of 55.60%. Most of the skin diseases were seen in the 5 to 13 years (school children) age group. The most common dermatoses was eczematous (36.63%), among eczema atopic diathesis was the commonest (17;20%) followed by hypersensitivity dermatoses (21.12%), genetic disorders (13.36%), disorders of genetic disorders (7.4%), sweat gland disorders (8.18%), pigmentary disorders (4.31%), papulo squamous disorders (4.74%), Nevi (6.46%). Conclusions: Eczematous dermatoses were the most commonly noted in the study, followed by hypersensitivity dermatoses. Atopic diathesis was the commonest endogenous eczemas. Acne, insect bite reaction and miliaria were the other common dermatoses. There was no significant association of various dermatoses with systemic diseases in the study.